First record of a Takayama bloom in Haizhou Bay in response to dissolved organic nitrogen and phosphorus. (May 2022) - Zhang, Qing-Chun; Wang, Yun-Feng; Song, Min-Jie; Wang, Jin-Xiu; Ji, Nan-Jing; Liu, Chao; Kong, Fan-Zhou; Yan, Tian; Yu, Ren-Cheng
Abstract: Since 1990s, harmful algal blooms (HABs) of Kareniaceae, primarily caused by species of Karenia and Karlodinium and rarely by Takayama species, have been substantially increasing in frequency and duration in the coastal waters of China. In this study, we recorded a bloom of high abundance of T. acrotrocha in the Haizhou Bay, the Yellow Sea in September 2020, which is the first record of a Takayama bloom in the temperate coastal waters of China. We found that high concentrations of DON and DOP accelerated the proliferation of T. acrotrocha in the Haizhou Bay. Intensive mariculture, and terrestrial nitrogen and phosphorus input may be responsible for the eutrophication in the Haizhou Bay featuring high concentrations of DON and DOP, and high DIN/DIP ratios. The results suggested that, under ocean warming, the HABs of Kareniaceae are becoming increasingly dominant in eutrophic temperate coasts with intensive mariculture activities. Highlights: Takayama acrotrocha bloom was firstly recorded in Haizhou Bay, China's temperate coastal bay. High organic nitrogen and phosphorus proliferated T. acrotrocha boom in Haizhou Bay. Intensive mariculture activities and input of terrestrial nutrients eutrophicated Haizhou Gulf.